2002
DOI: 10.1074/jbc.m112065200
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the p40-p47-p67 Complex in the Resting State of the NADPH Oxidase

Abstract: The phagocyte NADPH oxidase is a multiprotein enzyme whose subunits are partitioned between the cytosol and plasma membrane in resting cells. Upon exposure to appropriate stimuli multiple phosphorylation events in the cytosolic components take place, which induce rearrangements in a number of protein-protein interactions, ultimately leading to translocation of the cytoplasmic complex to the membrane. To understand the molecular mechanisms that underlie the assembly and activation process we have carried out a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(153 citation statements)
references
References 52 publications
6
144
0
3
Order By: Relevance
“…Our results are consistent with the latter hypothesis and indicate that the inhibitory effects of mAb NL7 binding to the 498 EKDVITGLK 506 epitope do not appear to directly affect membrane translocation of p47 phox , p67 phox , or Rac. However, there is evidence that cytosolic oxidase subunits may be translocated en bloc as a complex with p40 phox (36), and therefore dock to Cyt b by multiple contact sites. Therefore, obstruction of a single contact by mAb NL7 may be insufficient to prevent membrane translocation, but could inhibit functional interactions between Cyt b and the cytosolic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the latter hypothesis and indicate that the inhibitory effects of mAb NL7 binding to the 498 EKDVITGLK 506 epitope do not appear to directly affect membrane translocation of p47 phox , p67 phox , or Rac. However, there is evidence that cytosolic oxidase subunits may be translocated en bloc as a complex with p40 phox (36), and therefore dock to Cyt b by multiple contact sites. Therefore, obstruction of a single contact by mAb NL7 may be insufficient to prevent membrane translocation, but could inhibit functional interactions between Cyt b and the cytosolic factors.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest two mechanisms for the targeting p40 phox to phagosomes during Fc␥R-mediated phagocytosis: 1) p40 phox can bind initially to PI(3)P-enriched early endosomes, followed by their fusion to phagosomes, and/or 2) p40 phox can target directly to phagosomes, where PI(3)P is transiently produced during phagosytosis (Ellson et al, 2001a;Gillooly et al, 2001). Because the cytosolic phox proteins exist as a ternary complex (Kuribayashi et al, 2002;Lapouge et al, 2002), we propose a model for Nox2 complex assembly involving these spatiotemporal factors during the Fc␥R-mediated respiratory burst ( Figure 11): 1) in early stages, before phagosome sealing, p47 phox functions as the predominant carrier, mediating translocation of the ternary complex to newly forming phagosomes, 2) in later stages Model of activation and assembly of Nox2 system during phagocytosis. In the resting state, the ternary complex of p47 phox , p67 phox , and p40 phox is in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent study reported that p40 phox and p67 phox exist as a heterodimer in the resting state and that the p47 phox -containing ternary complex forms only after cell activation (Brown et al, 2003), most other studies to date indicate that the phox proteins exist as a stable 1:1:1 ternary cytoplasmic complex (p47 phox -p67 phox -p40 phox ) in their dephosphorylated state even without cell stimulation ( Figure 1A; Bolscher et al, 1989;Rotrosen and Leto, 1990;Lapouge et al, 2002;Kuribayashi et al, 2002). We examined ternary complex formation by using GFP-p67 phox coexpressed with p47 phox and p40 phox in COS-7 cells and confirmed that all three proteins exist at least partially in a complex that could be detected by immunoprecipitation with antibodies against any of these components ( Figure 1B).…”
Section: Accumulation Of P40 Phox (Px) At the Phagosome During Fc␥r-mmentioning
confidence: 99%
See 2 more Smart Citations